Peningkatan Branding UMKM dengan Memanfaatkan Media Pemberitaan dan Visual Produk - Setiawan, Elfa; Salsabila, Fahita P (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
PERURI as an institution that prints money and valuable documents in Indonesia, is not only committed to digital security services but also helps the government increase its productivity in serving the needs of the community more effectively through the development of MSMEs. PERURI has routinely provided assistance to MSMEs in adapting to digital processes that are in line with the Sustainable Development Goals (SDGs), namely providing decent work and supporting economic growth.The problems that become obstacles in the implementation of UMKM Go Digital initiated by government see technology and online marketing only through social media and assume digitalization as a marketing process oriented towards sales, not branding. This makes UMKM products less competitive in e-commerce. In addition, there are obstacles faced by UMKM actors related to digital assets in general, such as the internet users are more for entertainment, playing games, chatting media, lack of literacy in the use of IT for business and lack of maximum empowerment of the community for innovation and product development, especially UMKM. The training was held with the aim of increasing the competence of UMKM fostered by PERURI to be more literate in the digital world, which actually starts from building assets, to digital administrative documentation. Making UMKM fostered by PERURI more bankable.